PERAN PENYULUH PERTANIAN DALAM PEMBERDAYAAN KELOMPOK TANI MAHENEYAHA DAN KELOMPOK TANI IMANUEL DI KECAMATAN KABOLA - Emirensiana Latuan; Didiana Y. Molebila; Ferdinan Demang; James Duka (Partner, 2023)
The research was conducted by the Maheneyaha farmer group and Imanuel farmer group from March to May 2023. This study aims to determine the role of agricultural extension agents in empowerment and to determine the effect of the agricultural extension role on the empowerment of the Maheneyaha farmer group and the Imanuel farmer group. Data were analyzed using the percentage of achieving the maximum score as follows: the average score for all respondents divided by the maximum score and multiplied by 100%. The results obtained the role of extension workers as facilitators, motivators, communicators, educators and dynamicators scores are high.Keywords: Extension Role, Empowerment, Farmer Groups